1288 The effect of shift work on cardiometabolic health: findings from the atlantic path cohort study. (24th April 2018) - Sweeney, Ellen; Yu, Zhijie Michael; Dummer, Trevor JB; Cui, Yunsong; DeClercq, Vanessa; Forbes, Cynthia; Grandy, Scott A; Keats, Melanie; Parker, Louise; Adisesh, Anil
Abstract : Introduction: Contemporary work environments increasingly rely upon a 24 hour work cycle resulting in more employees exposed to shift work. 30% of working age Canadians work evening, night and rotating shifts, and 21% of workers in the European Union. Compared to regular daytime work, shift work has the potential for disturbing sleep patterns and disrupting circadian rhythms with adverse health effects. Methods: Participation was limited to volunteers from the Atlantic Canadian Provinces (Nova Scotia, New Brunswick, Newfoundland and Labrador, and Prince Edward Island). 12 413 participants, including 4155 shift workers and 8258 non-shift workers (matched 1:2 by age, sex, and education) from the Atlantic Partnership for Tomorrow's Health (PATH) study. Multiple general linear and logistic regression models were used to assess differences in body adiposity and self-reported cardiometabolic disease outcomes between shift workers and non-shift workers. Results: There was a significant increased risk of obesity and diabetes among shift workers compared to their matched controls. Shift workers were 18% more likely to be obese (95% CI: 9 to 29) and 8% more likely to have abdominal obesity (95% CI: 0 to 17). Shift workers were 31% more likely to have diabetes than non-shift workers (95% CI: 11 to 56). The strength of this association was further demonstrated by controlling for participants' fat mass index (FMI), which resulted in a 28% increased risk of diabetes among shift workers (95% CI: 2 to 60). Despite the increased likelihood of being physically active, regular night shift workers had higher levels of BMI, waist circumference, and fat mass compared with matched controls. Conclusion: Despite higher levels of physical activity and lower levels of sedentary behaviour, shift workers were more likely to have increased rates of diabetes and obesity and are subsequently at increased the risk of developing other chronic disease. The effects of shift work on cardiometabolic status may be independent of simple obesity.